1989
DOI: 10.1093/bja/62.2.164
|View full text |Cite
|
Sign up to set email alerts
|

Plain Bupivacaine: 0.5% or 0.25% for Spinal Analgesia?

Abstract: Plain 0.5% bupivacaine 3 ml was compared with plain 0.25% bupivacaine 6 ml for spinal anaesthesia during transurethral surgery in 40 patients. The solutions were injected over 30 s at the L3/4 space with the patient in the sitting position. The patient was kept sitting for 2 min, supine for 5 min and then placed in the lithotomy position. No significant differences were found in onset time, extent of cephalad spread, duration of sensory or motor blockade, or side effects. The use of a 0.5% plain solution of bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Van Zundert et al (17) reported that the anesthetic effect as well as the degree of motor block produced by 70 mg of spinal lidocaine was similar with solutions ranging from 0.5% to 10%. Nielsen et al (18) were not able to detect any difference in the onset and duration of sensory or motor block after 15 mg of isobaric 0.25% or 0.5% bupivacaine. Vucevic and Russell (19) have shown that 15 mg of spinal 0.125% isobaric bupivacaine produced similar final levels of block as compared to the same dose of 0.5% solution for Cesarean delivery.…”
Section: Discussionmentioning
confidence: 91%
“…Van Zundert et al (17) reported that the anesthetic effect as well as the degree of motor block produced by 70 mg of spinal lidocaine was similar with solutions ranging from 0.5% to 10%. Nielsen et al (18) were not able to detect any difference in the onset and duration of sensory or motor block after 15 mg of isobaric 0.25% or 0.5% bupivacaine. Vucevic and Russell (19) have shown that 15 mg of spinal 0.125% isobaric bupivacaine produced similar final levels of block as compared to the same dose of 0.5% solution for Cesarean delivery.…”
Section: Discussionmentioning
confidence: 91%
“…I n addition, a more predictable level of anaesthesia was achieved when a 0.125% solution was used (35). Similarly 3 ml of 0.5% plain bupivacaine and 6 ml of 0.25% bupivacaine injected with the patients in a horizontal or sitting position resulted in equal spinal blocks (36,37). Thus, the use of a more concentrated solution does not appear to confer any advantage over use of a less concentrated solution.…”
Section: Plain Bupivacainementioning
confidence: 99%
“…Complete motor blockade is generally achieved following the administration of plain bupivacaine in doses of 15 to 20 mg ( 12, 18, 19, 3 1, 33, 34). Dilution or warming of the solution before injection has no effect on the motor block (16,(35)(36)(37)(38). The motor blockade was shown to be more intense in the patients who were kept sitting, regardless of whether a solution of plain or hyperbaric bupivacaine was used (21).…”
Section: Suhlmary O F Factors Affecting T H E Spread Of the Blockmentioning
confidence: 99%
“…Comparison of the anesthetic effects of plain bupivacaine at a dose of 10 mg diluted in 1.3 ml or 2 ml, of 15 mg diluted in 2 ml or 3 ml and of 20 mg diluted in 2.7 ml and 4 ml did not reveal any significant difference (3). Even for higher volumes such as 15 mg of bupivacaine in 3 ml or 6 ml (14,15), 17.5 mg of bupivacaine in 3.5 ml, 7 ml or 10 ml (16), 12.5 mg of bupivacaine in 2.5 ml or 10 ml (7) and finally 10 mg of plain tetracaine in 1 ml, 2 ml or 4 ml (8), no difference was observed. Nevertheless, one study reported a cephalic sensory level significantly lower in patients receiving 15 mg of plain bupivacaine in 2 ml compared to those receiving the same dose in 3 ml, 6 ml and 9 ml (1 7 ) .…”
Section: Discussionmentioning
confidence: 99%